Securing Sustainable Digitalization: An Integrative Study on Data Privacy, Cybersecurity, and Business Continuity in SMEs - Lusiah, L.; Parulian, Edison (Manunggal Halim Jaya, 2025)
This study examines the interrelationship among data privacy practices, cybersecurity readiness, and business continuity planning in enhancing sustainable digitalization within small and medium-sized enterprises (SMEs). This study employs a quantitative descriptive approach using structured survey data collected from 250 SMEs operating in manufacturing, retail, and service sectors in Indonesia. The analysis was conducted using structural equation modeling to assess both direct and mediated relationships among the three digital capabilities and their influence on sustainability outcomes. The results reveal that data privacy practices significantly contribute to improving cybersecurity readiness, and cybersecurity readiness has a positive impact on the development of business continuity plans. Furthermore, business continuity planning mediates the effect of cybersecurity readiness on sustainable performance, which includes operational reliability, digital trust, and environmental responsibility. The findings of this study suggest that secure digital capabilities, when integrated systematically, enhance the long-term viability and resilience of SMEs operating in emerging markets. This research provides empirical evidence supporting a triadic framework linking digital security components with sustainability outcomes in resource-constrained settings.